(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The micro- and nanoplastic (MP/NP) contamination of freshwater systems has become a rapidly growing environmental and public health concern globally, yet rural groundwater and surface water of sub-Saharan Africa remain critically understudied. This first exploratory study in Aifam Owukpa, Ogbadibo Local Government Area (LGA), Benue State, Nigeria, characterises MP/NP contamination across 12 purposively selected water sources (streams, springs, and hand-dug wells) sampled during the rainy season (July–August 2025). Multi-stage membrane filtration (5 µm and 0.45 µm), hydrogen peroxide digestion, and sodium chloride density separation were applied for particle extraction. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy (Nicolet iS50, 4,000–400 cm⁻¹) was used for polymer identification, and Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDS; JEOL JSM-6610LV) provided morphological and elemental characterisation. Physicochemical parameters (pH, turbidity, electrical conductivity, biochemical oxygen demand, and total dissolved solids) were measured and benchmarked against WHO drinking-water quality guidelines. Microplastics were detected in 85% of sampling sites (11 of 12) at concentrations of 45–210 particles/L (mean: 112 ± 45 particles/L), with stream sites substantially exceeding wells and springs. Dominant polymers were polyethylene (40%), polypropylene (30%), polystyrene (15%), polyethylene terephthalate (10%), and polyvinyl chloride (5%). Morphological analysis identified fragments (55%), fibres (30%), and films (15%). Nanoplastic presence was inferred in 40% of samples via sub-micrometre spectral broadening; direct quantification using Py-GC/MS or nano-FTIR is strongly recommended for future work. Turbidity showed a strong positive correlation with MP abundance (r = 0.78, p < 0.01). SEM-EDS confirmed high carbon content (65–75% C) and weathering-consistent morphologies indicative of local secondary fragmentation. A GIS-based contamination hotspot map (Figure 11) spatially delineates high-, moderate-, and low-risk zones. The single-season design and absence of contaminant adsorption data are acknowledged limitations; future studies should incorporate comparative dry- and wet-season sampling, quantitative nanoplastic analysis, and heavy metal/persistent organic pollutant (POP) adsorption experiments. These findings establish a critical contamination baseline, underscoring the need for community-level plastic waste governance and integration of MP monitoring into Benue State water quality frameworks.